DNA double strand break repair as cellular response to genotoxic asarone isomers considering phase I metabolism. (August 2020) - Hermes, Lena; Haupenthal, Sabrina; Uebel, Thomas; Esselen, Melanie
Abstract: The phenylpropenes α -asarone and β- asarone are widely spread in the marsh plant Acorus calamus. Both isomers are classified as carcinogenic in rodents. However, the respective genotoxic mechanisms are not elucidated so far. The present study gives deeper insights into the genotoxic effects of asarone isomers as well as their known oxidative phase I metabolites, ( E )-3′-oxoasarone and asarone epoxide. We show that asarone metabolites highly increase DNA strand breaks after 1 h of incubation, markedly metabolic activation contributes to their carcinogenic mode of action. All test compounds act as aneugens and potently enhance the amounts of micronuclei in binuclear cells. However, a prolonged incubation time of 24 h results in a decrease of DNA damage. This work suggests that asarone metabolites also induce DNA double strand breaks, why we put a strong focus on homologous recombination and non-homologous end joining. The obtained results herein indicate that asarone epoxide-induced DNA strand breaks are repaired via a homologous repair pathway. Graphical abstract: Image 1 Highlights: Clastogenic events as well as aneuploidy contribute to asarone-induced genotoxicity. Metabolic activation of asarones is essential for their genotoxic potential. Homologous repair pathway as cellular response to asarone epoxide treatment.